34.2k views
4 votes
(6x3 + 3x² + 3) + (2x - 5x + 1)
the sum is?

(6x3 + 3x² + 3) + (2x - 5x + 1) the sum is?-example-1
User PEF
by
4.8k points

2 Answers

7 votes

Answer:

8x^3 + 3x^2 - 5x + 4 is the answer.

Explanation:

(6x^3 + 3x² + 3) + (2x^3 - 5x + 1)

6x^3 + 2x^3 = 8x^3

3x^2 + 0 = 3x^2

-5x + 0 = -5x

3 + 1 = 4

8x^3 + 3x^2 - 5x + 4 is the answer because you have to put all the terms that were solved together. This will lead to 8x^3 + 3x^2 - 5x + 4. And, standard form is ax^2 + bx + c. So, 8x^3 + 3x^2 - 5x + 4 is the answer.

8x^3 + 3x^2 - 5x + 4

Hope this helped,

Kavitha

User Niklas Peter
by
5.8k points
6 votes

Answer:

= 8x³ + 3x² - 5x + 4

Explanation:

(6x³ + 3x² + 3) + (2x³ - 5x + 1)

= 6x³ + 3x² + 3 + 2x³ - 5x + 1 remove parentheses

= 6x³ + 2x³ + 3x² - 5x + 1 group like terms

= 8x³ + 3x² - 5x + 3 + 1 add similar elements

= 8x³ + 3x² - 5x + 4

User Mekazu
by
5.1k points